Increased detection of suspected atrial fibrillation in elderly and female hypertensive patients through home blood pressure monitoring: the HOME-AF study. Issue 3 (March 2020) - Savvari, Paraskevi; Triantafyllidi, Helen; Skiadas, John; Kalogeropoulos, Petros; Menegas, Damianos; Manolis, Athanasios; Papoulidis, Neofitos; Andrikopoulos, George; Tsioufis, Konstantinos
Abstract : Background: Episodes of suspected atrial fibrillation are particularly frequent in essential hypertension. This study aimed to investigate the incidence of new suspected atrial fibrillation cases detected through home blood pressure (BP) screening among hypertensive patients. Association of new suspected atrial fibrillation cases with arterial hypertension (AH) phenotypes and the CHA2 DS2 -VASc score was also investigated. Methods: The prospective study recruited hypertensive patients at least 50 years old from private and hospital hypertensive clinics. An ECG was performed during the first visit. Microlife BP A6 PC was used to measure office and home BP for at least 3 and preferably 7 consecutive days. Results: A total of 2408 AH patients were recruited. Suspected atrial fibrillation was detected by BP monitor in 12.5% of patients. CHA2 DS2 -VASc was greater in hypertensive patients with suspected atrial fibrillation detection, as compared with all other hypertensive patients (3.3 ± 1.4 vs. 2.8 ± 1.4, P < 0.0001). Suspected atrial fibrillation detection was associated with advanced age (≥ 75 years, P < 0.0001) and female sex ( P = 0.01). A nonsignificant association between suspected atrial fibrillation detection and history of chronic heart failure/left ventricular dysfunction was observed ( P = 0.06). In the multivariate analysis, age and sex were the only independent risk factors with patients at least 75 years old having more than twice the risk of suspected atrial fibrillation compared with patients less than 64 years old. No differences between new suspected atrial fibrillation cases and AH phenotype (white coat/uncontrolled/masked hypertension) were identified. Conclusion: In our cohort of hypertensive patients, suspected atrial fibrillation was common particularly among elderly and female patients. These results underline the need for early suspected atrial fibrillation detection to minimize the increased thromboembolic risk associated with hypertension. Abstract : Supplemental Digital Content is available in the text